Role of protein kinase C in desensitization of spinal delta-opioid-mediated antinociception in the mouse. - Narita, M. (1996)
1. Receptor phosphorylation and down-regulation by protein kinases may be a key event initiating desensitization. The present studies were designed to investigate the effect of a potent protein kinase C (PKC) activator, phorbol 12,13-dibutyrate (PDBu), on antinociception induced by intrathecal (i.t.) administration of a selective delta-opioid receptor agonist [D-Ala2] deltorphin II in the male ICR mouse and on the specific binding of [3H]-[D-Ser2, Leu5]enkephalin-Thr6 (DSLET), a delta-opioid receptor ligand, in the crude synaptic membrane of the spinal cord. 2. Intrathecal (i.t.) pretreatment with PDBu at low doses, which injected alone did not affect the basal tail-flick latency, dose-dependently attenuated the antinociception induced by i.t. administration of [D-Ala2]deltorphin II. The attenuation of i.t.-administered [D-Ala2] deltorphin II-induced antinociception by PDBu was reversed in a dose-dependent manner by i.t. concomitant pretreatment with a specific PKC inhibitor, calphostin C. 3. In the binding experiment, incubation of the crude synaptic membrane of the spinal cord for 2 h at 25 degrees C with PDBu (0.03 to 10 microM) caused a dose-dependent inhibition of the [3H]-DSLET binding. Scatchard analysis of [3H]-DSLET binding revealed that PDBu at 10 microM displayed a 30.7% reduction in the number of [3H]-DSLET binding sites with no significant change in affinity, compared with the non-treatment control, indicating that the activation of membrane-bound PKC by PDBu causes a decrease in the number of specific delta-opioid agonist binding sites. 4. An i.t. injection of [D-Ala2]deltorphin II produced an acute antinociceptive tolerance to the antinociceptive effect of a subsequent i.t. challenge of [D-Ala2]deltorphin II. Concomitant pretreatment with calphostin C markedly prevented the development of acute tolerance to the i.t.-administered [D-Ala2]deltorphin II-induced antinociception. On the other hand, a highly selective protein kinase A (PKA) inhibitor, KT5720, did not have any effect on the development of acute tolerance to [D-Ala2]deltorphin II antinociception. 5. These findings suggest that a loss of specific delta-agonist binding by the activation of PKC by PDBu is involved in the PDBu-induced antinociceptive unresponsiveness to delta-opioid receptor agonist in the mouse spinal cord. Based on the acute tolerance studies, we propose that PKC, but not PKA, plays an important role in the process of homologous desensitization of the spinal delta-opioid receptor-mediated antinociception.